Design Of Antenna With Matching And Rectifying Circuit For Radio Frequency Energy Harvesting System - Zainuddin, Nur Aishah (2015)
Nowadays, the development of wireless communication has become more important and has received huge demands around the globe. As the technologies of wireless communication systems are evolving, the energy or power that is needed to operate these wireless devices are also increasing. However, limited natural power sources have stimulated a few alternatives of producing renewable energy, including the energy harvesting system. The purpose of this project was to design a radio frequency (RF) energy harvesting system to scavenge RF energy from the ambient. An RF energy harvesting device consists of three primary subsystems. The first subsystem is the receiving antenna, which is responsible for capturing all the RF energy that is later used to power the integrated embedded system. The second main subsystem is the matching circuit, which is used to match the impedance between antenna and rectifier in minimizing power loss, hence improving the efficiency of the overall system. Meanwhile, the third subsystem is the rectification circuitry, which efficiently converts the input RF power into DC output power. Each one of these three subsystems is integral to the operation of the entire harvester system. Thus, a 2.45GHz RF energy harvester was proposed. The presented work consisted of defining the characterizations of all subsystems and was preceded with optimized design process. The prototype of the system was then fabricated in-house for lab measurement and test. From the measurement that had been carried out, the RF energy system produced low DC voltage, which was applicable to operate low voltage applications and devices. The final design of antenna operated at 2.45GHz with 14.16dB gain and a strong directional radiation pattern, while the measured efficiency of the single stage and the cascaded rectifier were up to 13.99% and 42.26% respectively. The simulation and the measurement results were then compared. The antenna was designed with Computer Simulation Technology (CST) Studio suite 2011 software, whereas the rectifier and the matching circuit were designed with Agilent Technology Advanced Design System (ADS) 2011 software. From the measurement results obtained in this project, the integration between the antenna and the rectifying circuit was done successfully to obtain output DC voltage, and subsequently proved the concept of the RF energy harvesting system. The output result obtained from this system is adequate and should be able to operate some applications, for instance, sensors with appropriate supplying voltage to operate.